2018
DOI: 10.1049/iet-spr.2017.0140
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic EEG signal classification using optimum allocation based power spectral density estimation

Abstract: This study proposes a novel approach blending optimum allocation (OA) technique and spectral density estimation to analyse and classify epileptic electroencephalogram (EEG) signals. This study employs the OA to determine representative sample points from the original EEG data and then applies periodogram (PD), autoregressive (AR), and the mixture of PD and AR to extract the discriminative features from each OA sample group. The obtained feature sets are evaluated by three popular machine learning methods: supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Cross correlation, Complex network; Auto correlation; Cross-variances; Correlation dimension) [7][8][9][10][11], frequency domain feature (e.g. Fast Fourier Transform (FFT); Eigenvector; Autoregressive) [12][13][14], timefrequency domain features (e.g. Short Time Fourier Transform (STFT); Wavelet transform (WT); empirical mode decomposition (EMD)) [5,[15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Cross correlation, Complex network; Auto correlation; Cross-variances; Correlation dimension) [7][8][9][10][11], frequency domain feature (e.g. Fast Fourier Transform (FFT); Eigenvector; Autoregressive) [12][13][14], timefrequency domain features (e.g. Short Time Fourier Transform (STFT); Wavelet transform (WT); empirical mode decomposition (EMD)) [5,[15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…PSD, which estimates the distribution of power spectrum over frequency bins, is a well-established technique for quantitative analysis of EEG signals, as well as for epilepsy [ 8 , 39 ]. In this study, we first computed the PSD of pre- and postseizure via Welch's method and then statistically compared the PSD per electrode between the two conditions to uncover any potential differences using paired t -test.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies focusing on epileptic seizures found increased synchronization [ 4 6 ] and increased energy of brain waves [ 7 ] occur before the onset of epileptic seizure. The power spectral density (PSD) has been widely used to measure the fluctuating power of related epileptic activity [ 8 , 9 ]; for example, Bettus et al estimated the PSD difference between drug-resistant and drug-sensitive mesial temporal lobe epilepsy patients and found significantly decreased subtheta PSD in the drug-resistant group [ 10 ]. Additionally, nonlinear analyses have been widely used to uncover the dynamic information of the brain activity in epileptic patients (EPs) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The classifier in this research is the SVM, as the SVM classification complexity does not depend on the feature dimension, and it provides a global solution [ 28 , 29 , 30 ], which might be appropriate for epileptic EEG classification. Shiao et al [ 31 ] showed that the SVM-based seizure prediction system could achieve a robust prediction for preictal period and normal period iEEG signals from dogs with epilepsy.…”
Section: Introductionmentioning
confidence: 99%